2016
DOI: 10.1021/jacs.5b11031
|View full text |Cite
|
Sign up to set email alerts
|

Designer Ionic Liquids for Reversible Electrochemical Deposition/Dissolution of Magnesium

Abstract: Chelating ionic liquids (ILs), in which polyether chains are pendent from the organic pyrrolidinium cation of the ILs (PEGylated ILs), were prepared that facilitate reversible electrochemical deposition/dissolution of Mg from a Mg(BH4)2 source. Mg electrodeposition processes in two specific PEGylated-ILs were compared against that in the widely studied N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ionic liquid (BMPyrTFSI). The two chelating IL systems (one with a pendent polyether chain with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 51 publications
9
103
2
1
Order By: Relevance
“…For example, an in-depth study of Mg electrolyte decomposition elucidated that strong ion pairing in Mg electrolytes, coupled with the multiple-electron charge transfer reaction at the negative electrode, leads to concentrationdependent interfacial decomposition reactions. Recent experimental work on ionic liquid Mg electrolytes 77 similarly found that rational design of solvation structures is crucial to realizing novel systems with improved stability. Similar high-throughput computational efforts to search for more stable solvents for Li-air battery applications have also been undertaken.…”
Section: Energy Conversion: Thermoelectricsmentioning
confidence: 99%
“…For example, an in-depth study of Mg electrolyte decomposition elucidated that strong ion pairing in Mg electrolytes, coupled with the multiple-electron charge transfer reaction at the negative electrode, leads to concentrationdependent interfacial decomposition reactions. Recent experimental work on ionic liquid Mg electrolytes 77 similarly found that rational design of solvation structures is crucial to realizing novel systems with improved stability. Similar high-throughput computational efforts to search for more stable solvents for Li-air battery applications have also been undertaken.…”
Section: Energy Conversion: Thermoelectricsmentioning
confidence: 99%
“…demonstrated the first fully inorganic and halide-free Mg electrolytes enabling reversible Mg plating and stripping78. In an effort to improve the safety, attempts have been made to replace the flammable organic solvents by ionic liquids91011.…”
mentioning
confidence: 99%
“…[67] Watkins et al have recently designed ionic liquids with a polyether chain attached to an organic pyrolidinium cation to chelate the Mg ion. [68] Mg(BH 4 ) 2 dissolved in this ionic liquid showed superior coulombic efficiency and higher current density compared with the THF solutions. However, the low anodic stability (1.7 V versus Mg) makes Mg(BH 4 ) 2 unsuitable for practical Mg batteries.…”
Section: Electrolytes From Chloride-free Magnesium Saltsmentioning
confidence: 93%